Caso Smmelweis: al filo del paradigma médico moderno - Rita Bocó; Gisela Bulanikian (Mediações: Revista de Ciências Sociais, 2007)
Through this pages, we made an analysis on Semmelweis biography, which showed that he high death rate for women after giving birth was caused by infectious agents transmitted by contaminated hands of the doctors. From the beginning, we wondered what made of Semmelweis an accursed person. An insight to the first years of medical practice, when the professional knowledge was constructed and the concept of public health and hygienic arose, let us see what Semmelweis faced. Semmelweis discovery emerged during a historical period marked out by political instability and change, at the same time of the modern medical theory construction and the arising of a scientific paradigm, which validated and involved a dispute between orthodoxy and heterodoxy inside the medicine limits in the middle of the nineteenth century. In this way, it shows the opposition between the arising knowledge and the medical orthodoxy that he challenged it. We will try to analyze, from a new point of view, the doctor Semmelweis’s history, considered as a case of study about an individual who questioned the paradigms of the contemporary orthodox science. He pointed out an anomaly in the practice of the medicine. In the history of Semmelweis we can see the contradictions of the  rising medical knowledge and its practice that was trying to legitimate itself as the only scientific and accurate way of cure. Indeed he was questioned and damned. In spite of that, he became the father of the asepsis through the history. He opened new possibilities for an original understanding of infectious diseases.